Small intestinal bacterial overgrowth and intestinal methanogen overgrowth in gastrointestinal malignancies - Mechlińska, Aleksandra; Frąckiewicz, Katarzyna; Gładyś-Cieszyńska, Katarzyna; Buczek, Dagmara; Dziadziuszko, Rafał (Contemporary Oncology/Współczesna Onkologia, 2025)
Small intestinal bacterial overgrowth (SIBO) is defined by an abnormal proliferation of colon-specific bacteria in the small intestine, whereas intestinal methanogen overgrowth (IMO) manifests with an increase of methane-producing archaea, specifically Methanobrevibacter smithii. Both conditions can disrupt gastrointestinal motility and manifest with various clinical symptoms. Small intestinal bacterial overgrowth appears to increase the risk of malnutrition and negatively affect malabsorption of essential nutrients such as vitamin B12 and fat-soluble vitamins. This concern is particularly relevant for cancer patients as malnutrition can adversely affect treatment outcomes and mortality rates. Small intestinal bacterial overgrowth prevalence is 2.5–22% in the general population, with significantly higher rates observed in cancer patients, depending on a study, 65% of gastric and colorectal cancer patients, 63.3% of pancreatic cancer patients compared to 13.3% in healthy controls. Gastrointestinal complications, particularly in cases of gastrointestinal cancers, can arise from both the disease itself and its treatment. Managing symptoms becomes more challenging when SIBO occurs as its symptoms are often ambiguous and overlap with those of other conditions. This review summarizes the current state of knowledge on SIBO and IMO in gastrointestinal cancers. Current knowledge on SIBO and IMO, particularly in gastrointestinal cancer, is limited by the lack of validated diagnostic standards, evidence-based nutritional guidelines, and a focus on symptom control rather than underlying mechanisms. There is a need for research on recurrence despite treatment, as well as studies specifically targeting SIBO and IMO in cancer rather than as comorbidities. Future efforts should prioritize developing reliable diagnostics, understanding recurrence mechanisms, and exploring personalized therapies and nutritional interventions.